Engineering of Green Carbon Dots for Biomedical and Biotechnological Applications - Junjie Shang; Qian Zhou; Kehan Wang; Yunlin Wei (Molecules)
Carbon dots (CDs) are attracting increasing research attention due to their exceptional attributes, including their biocompatibility, water solubility, minimal toxicity, high photoluminescence, and easy functionalization. Green CDs, derived from natural sources such as fruits and vegetables, present advantages over conventionally produced CDs, such as cost-effectiveness, stability, simplicity, safety, and environmental friendliness. Various methods, including hydrothermal and microwave treatments, are used to synthesize green CDs, which demonstrate strong biocompatibility, stability, and luminescence. These properties give green CDs versatility in their biological applications, such as bioimaging, biosensing, and drug delivery. This review summarizes the prevalent synthesis methods and renewable sources regarding green CDs; examines their optical features; and explores their extensive biological applications, including in bioimaging, biosensing, drug/gene delivery, antimicrobial and antiviral effects, formatting of mathematical components, cancer diagnosis, and pharmaceutical formulations.